Determination of Organophosphorus Esters in Fall Protection Equipment by Accelerated Solvent Extraction and Solid-Phase Extraction Coupled with LC-MS/MS Detection - Haihong Li; Mingli Ye; Fangfang Wu; Xuyang Zhao; Lifeng Wang; Yili Wei; Shengyi Xie; Hairong Cui (Journal of Analytical Methods in Chemistry)
An analysis method was established to determine 14 organophosphorus ester (OPE) flame retardants in fall protection equipment by combining accelerated solvent extraction (ASE) and solid-phase extraction (SPE) with high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). The ASE parameters were optimized as follows: static extraction with acetonitrile at 80°C for 5 min for two cycles. The combined extract was purified with the ENVI-18 cartridge before further analysis. A HILIC column was used to separate the OPEs using an acetonitrile/water mixture as the mobile phase with the detection by the electrospray ionization mass spectrometry, which was operated under the positive mode. Under optimized conditions, the limit of detection for the target OPEs ranged in 0.015–1.33 ng/g, with a spike recovery of 71.6%–114% and a relative standard deviation of 0.8%–11.2%. The developed method was used to analyze OPEs in fall protection equipment (safety helmets and ropes), where OPEs were all detectable. Safety ropes displayed a higher concentration of OPEs than ones in safety helmets, with the pollutants being mainly triphenyl phosphate, 2-ethylhexyl diphenyl phosphate (EHDPP), tri(2-ethylhexyl) phosphate, and tri-n-butyl phosphate in the range of 11.07 ng/g‒815.53 ng/g. The EHDPP was the dominant compound in safety helmets with the concentration from 26.84 to 95.29 ng/g, while the other OPEs in safety helmets were lower than 5.136 ng/g. The potential health and environmental risks of these fall protection equipment during their use and disposal call for further attention.